Resting membrane potential is less negative in trabeculae from right atrial appendages of women, but action potential duration does not shorten with age. (March 2023) - Pecha, Simon; Ismaili, Djemail; Geelhoed, Bastiaan; Knaut, Michael; Reichenspurner, Hermann; Eschenhagen, Thomas; Schnabel, Renate B.; Christ, Torsten; Ravens, Ursula
Abstract: Aims: The incidence of atrial fibrillation (AF) increases with age. Women have a lower risk. Little is known on the impact of age, sex and clinical variables on action potentials (AP) recorded in right atrial tissue obtained during open heart surgery from patients in sinus rhythm (SR) and in longstanding AF. We here investigated whether age or sex have an impact on the shape of AP recorded in vitro from right atrial tissue. Methods: We performed multivariable analysis of individual AP data from trabeculae obtained during heart surgery of patients in SR ( n = 320) or in longstanding AF ( n = 201). AP were recorded by sharp microelectrodes at 37 °C at 1 Hz. Impact of clinical variables were modeled using a multivariable mixed model regression. Results: In SR, AP duration at 90% repolarization (APD90 ) increased with age. Lower ejection fraction and higher body mass index were associated with smaller action potential amplitude (APA) and maximum upstroke velocity (Vmax ). The use of beta-blockers was associated with larger APD90 . In tissues from women, resting membrane potential was less negative and APA as well as Vmax were smaller. Besides shorter APD20 in elderly patients, effects of age and sex on atrial AP were lost in AF. Conclusion: The higher probability to develop AF at advanced age cannot be explained by a shortening in APD90 . Less negative RMP and lower upstroke velocity might contribute to lower incidence of AF in women, which may be of clinical relevance. Graphical abstract: Unlabelled Image Highlights: We investigated the impact of clinical variables on human atrial action potential in a large dataset The higher probability to develop AF at advanced age cannot be explained by a shortening in right atrial tissue Less negative RMP and lower upstroke velocity might contribute to lower incidence of AF in women